(untitled) (Hekima Review, 2024)
Holy Ghost in the Catholic Machine makes a comprehensive, critical and insightful exploration of Catholic preaching, encompassing its sociological foundations, the structural reasons for its poor quality, and what can be done to improve it. Based on her experience as a Catholic, her expertise as a teacher of public speaking and web searches for Catholic preaching, Sigler inquires whether bad preaching in parishes is a manifestation of the conflicts and tensions between the three Weberian structures (charismatic, patrimonial and bureaucratic) in the Church generally and in Catholic priesthood specifically. These conflicts and tensions are referred to as structural divergence (SD). Sigler’s main objective is to explore SD in the Church’s structures, especially in preaching (p. 7).